Intraoperative evaluation of hepatic artery blood flow during pancreatoduodenectomy (HEPARFLOW): protocol of an exploratory study - Saeedi, Mohammed al; Frank-Moldzio, Leonie; Klauß, Miriam; Mayer, Philipp; Bruckner, Thomas; Khajeh, Elias; Golriz, Mohammad; Mehrabi, Arianeb; Knebel, Phillip; Diener, Markus K.; Büchler, Markus W.; Strobel, Oliver (International journal of surgery protocols, 2020)
Introduction: - Pancreatoduodenectomy is the treatment of choice for a range of benign and malignant diseases. The pancreatic head must be separated from its supplying vessels, especially the gastroduodenal artery, during this operation. However, dissection of the gastroduodenal artery can disturb blood supply to the liver and result in liver ischemia. There is currently no well-established algorithm to evaluate and ensure sufficient blood flow in patients with altered hepatic artery blood flow. To address this important issue, this study aims to establish a basis for assessing liver blood supply during pancreatoduodenectomy. Furthermore, factors influencing arterial blood flow and related postoperative complications will be evaluated. - Methods and analysis: - The HEPARFLOW study is a single institutional single-arm prospective exploratory observational clinical trial. All consecutive patients undergoing elective partial or total pancreatoduodenectomy will be screened for inclusion until 100 patients are enrolled. Blood flow in the proper hepatic artery, gastroduodenal artery, portal vein, and additional vessels supplying the liver will be measured during pancreatoduodenectomy using Doppler flowmetry. All patients will be followed up for 90 days after surgery. At each visit, standard clinical data, postoperative complications and mortality will be recorded. - Discussion: - This will be the first study to prospectively assess intraoperative flow rates of the hepatic artery and portal vein to evaluate liver blood supply during pancreatoduodenectomy. The preoperative and intraoperative factors influencing blood flow in the hepatic arteries will be identified. This study may also reveal the hemodynamic and clinical relevance of a compression of the celiac axis during pancreatoduodenectomy. - Ethics and dissemination: - This study was approved by the Ethics Committee of the University of Heidelberg (S-073/2018). The results will be published in a peer-reviewed journal and will be presented at medical meetings. - Highlights - - Assessment of flow rates of the hepatic artery during pancreatoduodenectomy. - Identification of pre- and intraoperative factors influencing liver blood flow. - Relevance of a celiac axis stenosis by pancreatoduodenectomy.
Gesehen am 01.06.2023